KAJIAN MEDIA TANAM DAN PEMBERIAN PUPUK P DAN K TERHADAP PERTUMBUHAN DAN HASIL TANAMAN TOMAT (Lycopersicum esculentum Mill.) - Akhmad Sopian; Rustam Baraq Noor; Nur Rohmat Amiruddin Qohhar (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2022)
Low soil fertility rates and not yet intensive crop cultivation have an impact on the declining trend on tomato production in the eastern multiplication. Low productivity of tomatoes due to low quality of seedlings and pest and disease attacks. Efforts to increase tomato production have been carried out, among others, by improving cultivation techniques, namely by improving the physical properties of the soil by adding organic materials and adding nutrients using inorganic fertilizers. The design of this study is; Complete randomized design with factorial analysis 2 x 4 and repetition as much as 3 times. In the first factor, the media mixture consists of 2 levels, namely T0 = Soil, T1 = Mixture of soil, manure, and chaff (2:1:1). The second factor is the combination of fertilizer K and P consists of 4 stages, namely: P0 = without fertilizer, P1 = 5gram KCL and 15grams SP-36, P2 = 10 grams KCL and 15 grams SP-36; P3 = 15 grams KCL and 15 grams SP-36. The number of polybags in the study is 24 with a per polybag size of 30 x 40 cm. The results showed the addition of manure and chaff gave clear results to the growth and production of tomatoes. The application of KCl and SP-36 fertilizers affect the high growth of plants but does not affect the production of tomato plants. Recommendations for the use of organic materials and KCL fertilizers, SP-36 is applied separately